Principles of surgical treatment of jaw osteomyelitis in patients with drug addiction - Malanchuk, Vladislav; Brodetskyi, Igor (Journal of Stomatology, 2016)
The aim of this study is to improve the effectiveness of treatment of drug addicted patients with osteomyelitis of the jaws by developing the basic principles of surgery. A total of eighty patients with chronic osteomyelitis of facial bones were examined and treated in the Kiev city clinical hospital №12 MFD №2 from 2012 to 2014. The average age of patients was 28.65 + 0,43 years, primarily males (77.2%). Medical history revealed that sixty patients (75%) had previously suffered from viral hepatitis (B, C), ten patients (12.5%) had been HIV-infected earlier. All the patients reported the use of the drug from the group of amphetamines – Pervitin («Vint”); however, half of the patients (50%) pointed out that they also used other drugs, including “shirka” (opiates) and “methadone” (derivative of heroin). During hospitalization, all the patients underwent a standard general medical examination, radiological evaluation (CT scanning) and a surgical intervention – sequestrectomy, sequestrnecrectomy, necrectomy, and resection of the affected part of the jaw.